A simplified model for understanding the performance of two-pot enclosed mud cookstoves. Issue 4 (6th October 2019) - Parajuli, Ayush; Agrawal, Saurabh; Tharu, Janak Kumar; Kamat, Anil Kumar; Jha, Ajay Kumar; Darlami, Hari Bahadur
Abstract: The objective of this study is to develop a mathematical model for a two-pot enclosed mud cookstove. A new model has been developed combining transient heat transfer, combustion chemistry and fluid flow. The model can be used for variation of the operation and design parameters. The model predicts performance parameters such as efficiency, boiling time, excess air ratio (EAR), transient wall, flame and char temperature. For an input power of 5.1 kW, the estimated overall efficiency, EAR and boiling time were 17.1%, 1.97 and 43 minutes, respectively. The model outcome is compared with experimental results. Further, 10 parameters are varied and their impact on cookstove performance is analysed. The optimum dimension for the door opening, combustion-chamber height and wall thickness are suggested. Therefore, this study can serve as an effective tool for cookstove design.